VARIABEL-VARIABEL YANG MEMENGARUHI WAKTU HINGGA SESEORANG MENGGUNAKAN NARKOBA PERTAMA KALI MENGGUNAKAN ANALISIS SURVIVAL - Widya Larasati; Mohammad Dokhi (Indonesian Journal of Statistics and Applications, 2020)
Indonesia is currently in a state of emergency of drugs because of its increasing abuse rate and its spread is widespread not only in big cities. The average of first drug use is in adolescence. This study aims to determine the variables that influence the time for someone to use drugs for the first time and the acceleration factor. The data analyzed by using Survival Analysis with the frailty variable is secondary data from BNN and Puslitkes UI survey. The result is, the average of first drug use in eight towns/districts of research locus was 18-year. Smoking, alcohol consumption, the environment, and gender are significant variables that influence the first drug use. A person who has smoked, use alcohol, lived in a drug-exposed environment, and male sex will have a resilient time not to use drugs faster with the acceleration factor of each variable are 0.3184, 0.3985, 0.3501, and 0.6773. The results conclude that regulations on cigarettes and alcohol need to be revisited since both influence drug initiation. In addition, prevention programs need to focus more on adolescents and young children so that they have strong self-defense from the influence of a drug-exposed environment.